DISTRIBUSI KAWASAN MANGROVE DI PULAU POTO KABUPATEN BINTAN MELALUI PENGINDERAAN JAUH - Zahidah; Mochamad Candra Wirawan Arief; Iwang Gumilar; Heti Herawati; Perdana Putra Kelana; Sri Een Hartatik (Bioma, 2023)
Mangrove is a unique vegetation type growing along the coastline and estuarine in tropical and subtropical countries. Mangroves in Indonesia are distributed in all major islands and small islands from Aceh on westside stretched to Papua on the east. This study is to monitor the mangrove area in Poto island a small island part of Kabupaten Bintan, Province of Riau Kepulauan. The difference in spatial resolution of remote sensing data Sentinel 2A and Pleiades were used to classify the land use including the mangrove area. The supervised classification by maximum likelihood classification showed the high-resolution image using Pleiades has higher accuracy for mangroves 81.99% and overall accuracy 90% (kappa 0.86) compared to Sentinel 2A for mangrove 72,34% and overall accuracy 80% (kappa 0.73). The mangrove area approximately 257 ha is strip-lining along the coastline with the largest mangrove area located on the southside of the island. Further research is to identify the mangroves’ formation and the serial condition of mangroves on the different times.